Scores From Overloaded Continuous Assessment Timetable: A Predictor Of Senior School Students Performance In Economics In Ilorin South - Bello Bolanle Muhinat (Anterior Jurnal, 2021)
This research work was carried out to investigate and ascertain how scores from overloaded continuous assessment (C.A) timetable predict senior school students’ academic performance in economics in Ilorin south local government. The study adopted an ex-post-facto design, and sample senior school (SS-II) students as the target population from nine randomly selected senior schools in Ilorin south local government. A hundred and eighty-two senior school students’ 2019 C.A and examination were sampled with the use of proforma. The data collected was analyzed using the mean score and Pearson’s Product Moment Correlation. The findings revealed that the students’ performance in economics C.A was low as a result of the overloaded in the C.A timetable. The result indicated that there was a significant relationship between senior school students’ C.A score and their economics examination at 0.05 level of significance. Based on these findings, it is recommended that school administrators should ensure that C.A timetable is properly designed and structured in a way that will enhance the performance of students in economics C.A in Ilorin south local government